Sistem Budidaya Ikan Lele (Clarias sp.) dalam Kolam Terpal dengan Teknologi Nano Bubble - Andriani, Yuli; Nurinsani, Rizka Amalia (Journal of Fish Nutrition, 2025)
Catfish (Clarias sp.) farming is one of the fastest-growing aquaculture sectors in Indonesia. However, a major challenge in this industry is water quality deterioration, particularly low dissolved oxygen levels, which can cause stress, disease, and reduced fish productivity. Nano bubble technology offers an innovative solution to increase dissolved oxygen levels more efficiently than conventional aeration methods. This study employs a literature review method by analyzing various journals and scientific sources related to the application of nano bubble technology in catfish farming. The findings indicate that nano bubble technology can increase dissolved oxygen levels by up to 30% compared to conventional aeration, reduce toxic compounds such as ammonia and nitrite, and improve feed efficiency and fish growth. Additionally, nano bubbles enhance fish survival rates by up to 40% and reduce water pollution. Given these benefits, this technology has the potential to be an effective solution for improving the productivity and sustainability of catfish farming in Indonesia.